2015
DOI: 10.1039/c5ob01020a
|View full text |Cite
|
Sign up to set email alerts
|

An efficient one pot regioselective synthesis of a 3,3′-spiro-phosphonylpyrazole-oxindole framework via base mediated [1,3]-dipolar cycloaddition reaction of the Bestmann–Ohira reagent with methyleneindolinones

Abstract: A one pot, highly regioselective synthesis of racemic 3,3'-spiro-phosphonylpyrazole-oxindole by 1,3-dipolar cycloaddition of an in situ generated anion of dialkyl 1-diazomethylphosphonate from the Bestmann-Ohira reagent (BOR) & methyleneindolinones has been developed. The synthesis affords the highly functionalized pyrazole scaffolds in good yields with excellent regioselectivity under mild reaction conditions within a short reaction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Compounds 13 40 and 14 41 were prepared according to literature. Spectroscopic data for compounds 1, 42 2, 43 3, 44 4, 45 5, 46 8, 47 9, 48 were in agreement with literature values.…”
Section: General Procedures For the Synthesis Of Compounds 10-12supporting
confidence: 89%
“…Compounds 13 40 and 14 41 were prepared according to literature. Spectroscopic data for compounds 1, 42 2, 43 3, 44 4, 45 5, 46 8, 47 9, 48 were in agreement with literature values.…”
Section: General Procedures For the Synthesis Of Compounds 10-12supporting
confidence: 89%
“…Contemporarily, Suryavanshi and co-workers also reported a base promoted 1,3-dipolar cycloaddition reaction of BOR with methyleneindolinones to obtain a diverse range of 3,3'spiro-phosphonylpyrazole-oxindoles in good yields. [21] Our continued efforts towards the synthesis of spiropyrazole based scaffolds prompted us to employ a variety of activated olefins for the 1,3-dipolar cycloaddition reaction with diazomethylphosphonate (DAMP) anion. Even though the Seyferth-Gilbert reagent has been extensively employed for the construction of phosphonylpyrazoles, the reports to access spiropyrazolines are quite scarce.…”
Section: Synthesis Of Pyrazolesmentioning
confidence: 99%
“…reported in 2015 a one‐pot highly regioselective 1,3‐dipolar cycloaddition reaction with BOR, giving a facile procedure to access racemic 3,3′‐spiro‐phosphonylpyrazole‐oxindoles. Conditions screening indicated that the use of KOH as base could promote the formation of 423 in generally good yields within only 10 min (Scheme ) . The mechanism might involve the initial cycloaddition of 422 and 412 to afford pyrazoline 424 .…”
Section: Reactions Involving Heterocyclic Ring Formationmentioning
confidence: 99%